2012
DOI: 10.1097/grf.0b013e3182510a73
|View full text |Cite
|
Sign up to set email alerts
|

Medical Management of Ectopic Pregnancy

Abstract: Medical management has become increasingly popular in the treatment of ectopic pregnancy. Given its convenience, for many it is used as a first line treatment, but this is not always the optimal choice for the patient. It is important to understand the options for medical treatment and when it is appropriate to treat a particular patient with medical management, or when one should opt for surgical management. This review outlines the different regimens for methotrexate administration and the associated risks a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
81
1
3

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(85 citation statements)
references
References 24 publications
0
81
1
3
Order By: Relevance
“…[12] Gaddagi et al [13] and Porwal S et al [14] showed that the incidence can be 1 per rate of EP has been reduced from 0.5 to 1.15 per 100 maternal deaths due to rapid diagnosis of EP. [15] The combination ultrasonography findings and serum β hCG level can help in rapid diagnosis. But in rural set up these rapid tests cannot be always available so we require few alternative methods to diagnose or to atleast give hint towards the diagnosis of ectopic pregnancy.…”
Section: Discussionmentioning
confidence: 99%
“…[12] Gaddagi et al [13] and Porwal S et al [14] showed that the incidence can be 1 per rate of EP has been reduced from 0.5 to 1.15 per 100 maternal deaths due to rapid diagnosis of EP. [15] The combination ultrasonography findings and serum β hCG level can help in rapid diagnosis. But in rural set up these rapid tests cannot be always available so we require few alternative methods to diagnose or to atleast give hint towards the diagnosis of ectopic pregnancy.…”
Section: Discussionmentioning
confidence: 99%
“… Normal complete blood count and LFTs, Creatinine. 3 When administering methotrexate therapy, it is essential to remain aware of the risks and side effects of medical management. Rupture of ectopic pregnancy during methotrexate treatment ranges from 7% -14%.…”
Section: Patient Selectionsmentioning
confidence: 99%
“…Mtx is also given in a multidose regimen of daily 1 mg/kg intramuscularly, alternating with 0.1 mg/kg of folinic acid intramuscularly for up to 4 doses or 2 dose regimen where 2 doses of Mtx was injected on day 0 and day 4 while continuing the same surveillance of human chorionic gonadotropin (hCG) with a single-dose protocol (on days 4 and 7) without folic acid. All these regimes are effective and safe with reported success rates of 65-94% and have minimal side effects [2][3][4].…”
Section: Introductionmentioning
confidence: 99%
“…Data about the Mtx treatment in patients with (βhCG) > 5,000 mIU/mL in the literature is relatively scarce because majority of those patients undergo surgery [2,3,7,8]. In this study, to the selected patients with high initial serum (βhCG; between 5,042 and 31,114 mIU/mL) who asked medical therapy, multiple doses of Mtx (1 mg/kg) with folinic acid rescue were given on an individualized basis.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation